Everyday learning about talking - Campbell, J. (Watson, A.C.T. : c)
The very early years of children's lives have been shown to be crucial to their development of language and their subsequent capacity to take advantage of preschool and school programs.In Everyday learning about talking, experienced educator and author Julie Campbell explains the stages in language development and how the involvement of children in listening to and participating in family conversations, especially before the age of three, enhances their capacity to learn to talk.Suggestions for simple word games to use as a starting point are also included.The progression of young children from joining in with a few simple words to actively contributing to detailed conversations is a delightful aspect of early development. This book shows parents, carers and educators what to expect along the way and how to enhance children's skills in this area
Includes bibliographical references.
Keywords: Infants; Language acquisition; Preschool children; Speech; Toddlers; Early childhood education